2014
DOI: 10.2147/jmdh.s68555
|View full text |Cite
|
Sign up to set email alerts
|

Networks of trainees: examining the effects of attending an interdisciplinary research training camp on the careers of new obesity scholars

Abstract: Students training in obesity research, prevention, and management face the challenge of developing expertise in their chosen academic field while at the same time recognizing that obesity is a complex issue that requires a multidisciplinary and multisectoral approach. In appreciation of this challenge, the Canadian Obesity Network (CON) has run an interdisciplinary summer training camp for graduate students, new career researchers, and clinicians for the past 8 years. This paper evaluates the effects of attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Teamwork and collaboration, broad conceptual knowledge of the research discipline, comprehensive understanding of their research field, communication, critical thinking, research design, research ethics, and knowledge transfer (Burgess et al, 2018;Verderame et al, 2018) have all been identified as core competencies for researchers. Due to the inherent complexity of health issues, there is also an increasing importance in openness and the capacity for cross-disciplinary work within health research (Burgess et al, 2018;Godley, Glenn, Sharma, & Spence, 2014). ere is, however, a paucity of scholarly literature focused on the development and implementation of practical strategies for research trainee competency building.…”
Section: Researcher Competenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teamwork and collaboration, broad conceptual knowledge of the research discipline, comprehensive understanding of their research field, communication, critical thinking, research design, research ethics, and knowledge transfer (Burgess et al, 2018;Verderame et al, 2018) have all been identified as core competencies for researchers. Due to the inherent complexity of health issues, there is also an increasing importance in openness and the capacity for cross-disciplinary work within health research (Burgess et al, 2018;Godley, Glenn, Sharma, & Spence, 2014). ere is, however, a paucity of scholarly literature focused on the development and implementation of practical strategies for research trainee competency building.…”
Section: Researcher Competenciesmentioning
confidence: 99%
“…Although effective, the competence-building strategies put forward by Carr et al (2018) and journal club formats described by Vadaparampil et al (2014) and Godley et al (2014) are resource intensive. Executing these strategies would not be feasible within most research institute settings, where the responsibility for competency-building activities outside of the scientist-trainee relationship is held by the trainees themselves.…”
Section: Journal Clubs As a Competency Buildermentioning
confidence: 99%
“…Although initiating an interdisciplinary research program can be difficult because of institutional or departmental silos, 12 such programs are highly beneficial to trainees. Through participating in an interdisciplinary research program, BIRCWH scholars gain an appreciation for the methodology and knowledge of other disciplines.…”
Section: Building Interdisciplinary Research Careers In Women’s Healtmentioning
confidence: 99%
“…Through participating in an interdisciplinary research program, BIRCWH scholars gain an appreciation for the methodology and knowledge of other disciplines. 12 Further, interdisciplinary research provides an opportunity to grow and maintain a professional network, 13 and larger network reach typically leads to more publications and a higher h -index. 14 Indeed, there is evidence that participation in the BIRCWH program may be a positive contributor to later professional success, as indicated by the number of BIRCWH scholars receiving subsequent NIH funding.…”
Section: Building Interdisciplinary Research Careers In Women’s Healtmentioning
confidence: 99%